2023
DOI: 10.1002/cncr.35111
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as a booster or obstacle of immunotherapy in patients with non–small cell lung cancer and diabetes mellitus

Ming‐Cheng Guan,
Qian Ding,
Jing Ning
et al.

Abstract: We read the article by Leshem et al. 1 with great interest. In a retrospective study, the authors estimated the impact of diabetes mellitus on the efficacy of pembrolizumab in patients with metastatic non-small cell lung cancer (NSCLC). They demonstrated significantly shorter overall survival (OS) and progression-free survival (PFS) for patients with diabetes versus those without diabetes, and diabetes mellitus was identified as an independent risk factor for shorter PFS and OS. It followed that immunotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Chronic proton pump inhibitor use was also found to be adversely associated with GI irAEs in a cohort of 363 patients who received ICI (HR 13.22, 95% CI 3.11–56.10) [ 138 ]. Exposure to metformin, a drug used for type 2 diabetes mellitus, was recently shown to be associated with an increased risk of death compared to other non-insulin hypoglycemic agents despite its presumed antitumor and immunomodulating effects [ 139 , 140 , 141 ]. Further studies are needed to elucidate the causality of metformin and observed mortality, and whether this is associated with irAEs.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Chronic proton pump inhibitor use was also found to be adversely associated with GI irAEs in a cohort of 363 patients who received ICI (HR 13.22, 95% CI 3.11–56.10) [ 138 ]. Exposure to metformin, a drug used for type 2 diabetes mellitus, was recently shown to be associated with an increased risk of death compared to other non-insulin hypoglycemic agents despite its presumed antitumor and immunomodulating effects [ 139 , 140 , 141 ]. Further studies are needed to elucidate the causality of metformin and observed mortality, and whether this is associated with irAEs.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%